Attitudes of cannabis growers to regulation of cannabis cultivation under a non-prohibition cannabis model - Lenton, Simon; Frank, V.; Barratt, Monica; Dahl, H.; Potter, G. (Elsevier, 2015)
Background: How cannabis cultivation is dealt with under various examples of cannabis legalization or regulation is an important consideration in design of such schemes. This study aimed to (i) investigate support among current or recent cannabis growers, for various potential policy options for cannabis cultivation if prohibition were repealed, and (ii) explore the support for these options across countries, scale of growing operations, demographics, drug use and cannabis supply involvement variables. Methods: This study utilized data from the online web survey of largely 'small-scale' cannabis cultivators, aged 18. yrs and over, in eleven countries conducted by the Global Cannabis Cultivation Research Consortium (GCCRC). Data from 1722 current and recent cannabis growers in Australia, Denmark and the UK, who were all asked about policy, were included in the analysis. It investigated support for various frameworks for cultivation: (no regulation (. free market); adult only; growing licenses; restrictions on plant numbers; licensed business-only sale; approved commercial growing; etc.). Among current growers, support for these options were compared across countries, across scale of growing operations, and by demographics, drug use and crime variables. Results: Although there were some between country differences in support for the various policy options, what was striking was the similarity of the proportions for each of the eight most popular policy options. Among current growers, many of these positions were predicted by demographic, drug use and cannabis growing variables which were conceptually congruent with these positions. Conclusion: The results have relevance for the provisions regarding cannabis cultivation in the design of new non-prohibitionist models of cannabis which are increasingly under consideration. It should be of interest to policy makers, drug policy researchers, law enforcement and cannabis cultivators.